IC (Intermediate Course) CMHN (Community Mental Health Nursing) Movement for Posyandu Cadres Towards a Mentally Healty Alert Village Di Jorong Balai Sabuah Batipuh Ateh Kabupaten Tanah Datar - Afnuhazi, Ridhyalla; Asman, Aulia; Asmara, Rini; Sari, Syafyu (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
Abstract: The Ministry of Health's Strategic Plan explains that Indonesia's vision for health development among others, is to mobilize and empower the community to live a healthy life, improve access to quality health services, improve surveillance, monitoring and to quality health services, improving surveillance, monitoring and health information, and increasing community empowerment. health information and improving community empowerment. The existence of community empowerment This community empowerment is very much in line with the concept of Community Mental Health Nursing(Community Mental Health Nursing or CMHN), especially in the IC CMHN, namely the existence of community participation in screening efforts. community participation in screening, improvement, prevention, recovery and rehabilitation efforts, especially mental health. health, especially mental health. IC CMHN is a form of community mental health care program that empowering the community independently to detect and seek improvement, maintenance and recovery of the mental health of their community through the existence of mental health cadres who collaborate with CMHN nurses at the puskesmas. In the UPT Puskesmas working area Batipuh I, especially in Jorong Balai Sabuah, there is no mental health cadre. Objective of the Community Partnership Program Community Partnership Program is the formation of mental health cadres who care about mental health. To To achieve this, it is necessary to organize the formation, training, and mentoring of health cadres at the Bambu Kuning Posyandu. for Health Cadres at Posyandu Bambu Kuning Jorong Balai Sabuah Batipuh Ateh. Training that will be given to health cadres in the form of screening for mental disorders in the community, psychosocial problems, and mental health. psychosocial problems, and mental health, assisting the recovery of clients who have been hospitalized, and being alert to the emergence of mental health problems in the community. to the emergence of mental health problems in the community. The target outputs resulting from the Community Partnership Program include: Package on IC CMHN that is published through accredited national scientific journals, articles in mass media, posters, ± 5 minutes of video implementation and books with ISBN. The technology package is in the form of community skills in the knowledge of how to detect or screen, assist in the recovery of clients experiencing mental disorders, and alert to the emergence of mental health problems. Creation of WEB about the IC CMHN movement. Certificate containing information that the cadre has competent to perform IC CMHN.